The Influence of Perceived Value and Country of Origin Image on the Purchase Decision of Foreign Skincare Products Among Generation Z: A Perspective of Islamic Financial Management - Ratih Dwi Rahmawati; Ahdiyat Agus Susila; Anik Gita Yuana (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the influence of perceived value and country of origin image on the purchase decision of foreign skincare products among Generation Z, with sharia consumption rationality as a moderating variable. The research employed a quantitative approach with 99 respondents selected through purposive sampling. Data were analyzed using Moderated Regression Analysis (MRA) with Robust Standard Error (HC3). The results indicate that perceived value does not have a significant effect on purchase decisions. In contrast, country of origin image and sharia consumption rationality have a positive and significant effect. Furthermore, sharia consumption rationality was not found to moderate the relationships between the variables studied. These findings suggest that Generation Z's purchase decisions for foreign skincare products are more influenced by the country of origin image of the product and the level of sharia consumption rationality than by the perceived value.